O & L Jurutera Perunding Sdn. Bhd. / Nurul Nadiah Mahiran - Mahiran, Nurul Nadiah (Faculty of Civi Engineering, 2017)
This report is about my industrial training that | have been going through for two month, which is 7 weeks. The place where | having my industrial training is at 0 & L Jurutera Perunding Sdn Bhd company. I choose this place as my location for industrial training is because this company was suggest by my own father due to this consultant is his friend company and for sure it near to my home as well. The reason I choose to do my internship privately because | believe that I will gain a lot of experiences and of course knowledge about being an engineer . This internship give me an opportunity to learn and develop new Sets of skills.